The Effectiveness of Kesum Leaves (Polygonum Minus) In Reducing of Free Fatty Acids In Used Cooking Oil - Ratnawaty, Gervacia Jenny; Indrawati, Ratih (Politeknik Negeri Ujung Pandang, 2020)
This study aims to determine the effect of adding kesum leaves (polygonum minus) to used cooking oil on reducing levels of free fatty acids. This type of research is quasi experimental. The population in this study is used cooking oil and the sample used is used cooking oil that has been added with the leaves of kesum with 5 treatments and replicated 5 times so that the total sample is 25.From the results, it was found that the average reduction in free fatty acid levels in used cooking oil before adding the leaves of kesum was 7,12%, which had added kesum leaves as much as 20 grams of 6.93%, 40 grams of 5.36%, 60 gr at 3.93%, 80 gr at 3.26% and 100 gr at 1.62%. The results of the analysis using linear regression test, it is known that the addition of 20 grams and 40 grams of p-value is 0.026 and 0.021 (p <0.05), respectively, so Ha is accepted, that is, there is a relationship between the effectiveness of leaves of kesum (polygonum minus) in reducing levels of fatty acid numbers. free of used cooking oil, namely the addition of 20 and 40 grams. Whereas in the addition of 60, 80 and 100 grams of kesum leaves there was no relationship that was shown with a p value> 0.05.